Assessing dengue outbreak areas using vector surveillance in north east district, Penang Island, Malaysia - Mohiddin, Ahmad; Jaal, Zairi; Md Lasim, Asmalia; Dieng, Hamady; Wan Musthapa, Wan Fatma Zuharah (Elsevier, 2015)
Objective: To understand the efficacy of ovitrap surveillance and its implementation on monitoring reflection upon case occurrence in relation to climate variables. Methods: We used routinely setup ovitrap surveillance to monitor the mosquito populations in previous outbreak areas. Ovitraps were installed weekly at three localities that experienced high number of dengue cases (Flat Hamna, Kampung Sungai Gelugor and Kampung Tanjung Tokong) from January 2010 to February 2011. Ovitraps and paddles were brought back to the laboratory and all of the water contents were poured into an enamel pan. Aged tap water was added into the enamel pan and eggs were allowed to hatch. The hatching larvae were counted after 3 days. The hatched larvae were identified at the 3rd instar larval stage. The ovitrap indices and mean number of larvae were analyzed using student t-test and One-way ANOVA. Spearmen’s rank correlation coefficient was used to determine the relation between meteorology variables and dengue fever cases. Results: Aedes albopictus was found as dominant species followed by Aedes aegypti recorded in all three study areas. Aedes aegypti preferred to breed outdoor with larvae collection, which was higher than indoor (72.37%). There was a positive correlation between the ovitrap index with the rainfall and humidity except in Kampung Tanjung Tokong. Our result also showed negative correlation between temperature and ovitrap index in all localities.